2021
DOI: 10.1177/03635465211047861
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Initial Tensioning Force of an ACL Graft Results in a Higher Graft Force After Screw Fixation Irrespective of the Screw Diameter: A Biomechanical Study

Abstract: Background: The intra-articular graft force (IAGF) in anterior cruciate ligament reconstruction decreases quickly over the first hours after surgery. Nevertheless, little is known about whether the initial extra-articular tensioning force (EATF) and screw diameter affect the graft force after fixation. Purpose: To investigate the effects of different EATFs on the IAGF of a soft tissue graft fixated via a bioabsorbable interference screw over 100 minutes after fixation and to evaluate the effects of different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“… 25 , 32 , 37 Although a relatively wide safe window for initial graft tension seems to exist, a higher tensioning force in laboratory studies was shown to better compensate graft tension loss due to the time-dependent viscoelastic behavior of the soft tissue graft. 24 , 27 , 36 In the current study, femoral-sided graft insertion within an adequate intratunnel graft portion until tunnel docking replicated an optimized clinical condition for graft ingrowth until final healing. Femoral-sided ALD suture knot tying was avoided in this study in accordance with the clinical requirements for simplified intraoperative workflow and reduced danger of postoperative knot irritation of surrounding soft tissue.…”
Section: Discussionmentioning
confidence: 57%
“… 25 , 32 , 37 Although a relatively wide safe window for initial graft tension seems to exist, a higher tensioning force in laboratory studies was shown to better compensate graft tension loss due to the time-dependent viscoelastic behavior of the soft tissue graft. 24 , 27 , 36 In the current study, femoral-sided graft insertion within an adequate intratunnel graft portion until tunnel docking replicated an optimized clinical condition for graft ingrowth until final healing. Femoral-sided ALD suture knot tying was avoided in this study in accordance with the clinical requirements for simplified intraoperative workflow and reduced danger of postoperative knot irritation of surrounding soft tissue.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, as the femur-graft-tibia complex undergoes load relaxation again, the tension may decrease after final graft fixation at the tibia [32]. In a recent cadaveric study, an initial extra-articular tensioning force of more than 80 N was associated with a significantly larger intra-articular graft force [33]. In another recent cadaveric study by Nishizawa et al, the authors observed that the intra-articular tension on the graft is significantly higher than the graft tension measured on an extra-articular device [34].…”
Section: Discussionmentioning
confidence: 99%